Antitumoral Drug Potential of Tryptophan-Betaxanthin and Related Plant Betalains in the Caenorhabditis elegans Tumoral Model - Paula Henarejos-Escudero; Samanta Hernández-García; M. Alejandra Guerrero-Rubio; Francisco García-Carmona; Fernando Gandía-Herrero (MDPI AG, 2020)
Betalains are plants pigments identified as potent antioxidant molecules, naturally present in foods like beetroot and prickly pears. Although activities described for betalain-containing formulations include cancer prevention and treatment, the use of extracts instead of purified pigments has avoided the investigation of the real chemopreventive and chemotherapeutic potential of these phytochemicals. Three betalain-rich extracts and six individual pure betalains were used in this work to characterize the activity and to explore possible molecular mechanisms. The animal model Caenorhabditis elegans (tumoral strain JK1466) was used to evaluate the effect of betalains as chemotherapeutics drugs. An objective evaluation method of tumor growth in C. elegans has been developed to assess the possible antitumoral activity of the different treatments. This protocol allowed a fast and reliable screening of possible antitumoral drugs. Among the betalains tested, tryptophan-betaxanthin reduced tumor size by 56.4% and prolonged the animal's lifespan by 9.3%, indicating high effectiveness and low toxicity. Structure-activity relationships are considered. Assays with mutant strains of C. elegans showed that the mechanism underlying these effects was the modulation of the DAF-16 transcription factor and the insulin signaling pathway. Our results indicate that tryptophan-betaxanthin and related betalains are strong candidates as antitumoral molecules in cancer treatment.